Analysis of Potential Development of Bahari, Muara Nauli Beach, Central Tapanuli District, North Sumatera Province - Kurnia, Fadly Agra; Samiaji, Joko; Yoswaty, Dessy (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This research was conducted in November 2019 at Muara Nauli Beach, Central Tapanuli Regency, North Sumatra Province. With the aims to determine the potential of marine ecotourism at Muara Nauli Beach and its development strategy. The method used in this study was a survey method by collecting qualitative and quantitative data in the form of interviews, questionnaires and direct measurement. The research location was divided into 3 station points, namely Station I near the river estuary, Station II where swimming and relaxing activities are located, Station III is located at the location of tourist facilities. The results showed that the tourism suitability index, the suitability value for tourism activities at Muara Nauli Beach, were in the very suitable category (S1), with values ranging from 96.43-97.61% and an average value of 97.22%. This value was included in the very suitable category as ecotourism and can be used as marine ecotourism. Muara Nauli Beach has an attraction of natural beauty in the forms of white sand, turbid blue waters, spot for swimming activities. Muara Nauli Beach also has a large and beautiful estuary that can be used for fishing and a spot for taking pictures and viewing of the sunset. The natural beauty makes a great opportunity for Muara Nauli Beach to be developed as a marine ecotourism area